LILLI RECHT - THE FORGOTTEN TREASURE OF THE OLOMOUC NEW OBJECTIVITY? - Kamenská, Markéta (Bohemica Olomucensia, 2021)
This article is based on the analysis in the thesis Lilli Recht and Mascha Kaléko, Two Poetesses of The New Objectivity (2021) and introduces The New Objectivity as an art direction, under which we can classify Lilli Recht nowadays almost forgotten author born in Olomouc. It describes The German Moravian Literature too as an important context of the life and work of Lilli Recht. The thesis has shown that the lyrical work of Lilli Recht is on the comparable level with the well-known poems of The New Objectivity und therefor we can consider the author to be the "treasure" of Olomouc New Objectivity. Because The New Objectivity does not appear very often in the context of our literature, the discovery of this author und her specific writing style is even more crucial.
Keywords: Lilli Recht; Mascha Kaléko; The New Objectivity; The German Moravian Literature; The Literature of The New Objectivity; The Poetry of The New Objectivity